ANALISIS NERACA AIR SEBAGAI UPAYA PENINGKATAN PEMANFAATAN AIR DI DAERAH ALIRAN SUNGAI MARTAPURA, PROVINSI KALIMANTAN SELATAN - Kiki Frida Sulistyani; Danang Bimo Irianto (Jurnal Qua Teknika, 2022)
The water balance in Martapura watershed is calculated to maximise water utilization. The Martapura Watershed is located in Banjar Regency and Banjarmasin City. The utilization of Martapura River are for 6 irrigation area, ​​641 Ha fish ponds area, 25 Swamp Irrigation Areas, 7 intake for raw water, 8 intakes for industry and river maintenance using Q95%.Rainfall runoff calculation using the FJ Mock method. The Martapura watershed is divided into 10 sub-watersheds (sub-watershed A to sub-watershed J). Sub-watershed A is Riam Kanan Dam, so it uses outflow reservoir as inflow discharge. the average reservoir outflow discharge is 39,52 m3/s, except for the period from November I to December II. Reliable discharge calculation of water availability for other sub-watersheds uses flow duration curve method, for wet year discharge (Q20%), normal year discharge (Q50%) and dry year discharge (Q80%). Calculation of water balance using 2 type water demand, current water demand and potential increasing water demand. There are 3 type of water availability that used in this calculation, dry year discharge, wet year and normal year. The water balance is calculated for each sub-watershed and and followed with the calculation for the total Martapura watershed. The results of the calculation of the dry year water balance in total for one watershed are still in surplus, but the result calculation for each sub-watershed show that there is a deficit in sub-watershed B in November I – December II, due to the small discharge from Riam Kanan Reservoir. In dry years, raw and industrial water flow cannot be increased, but irrigation can be increased in the second planting season, covering an area of ​​2.065 ha in DI and 5.416 ha in DIR. The calculation of the water balance in a normal year, in total the Martapura watershed is still in surplus, but the result calculation for each sub-watershed shows that there is a deficit in sub-watershed B in November I - December II. In normal year discharge, raw water can still be increased by 1,11 m3/sec and irrigation area increase in planting season I, 328 Ha and 2.912 Ha in planting season II, ​​while in swamp irrigation area there is an increase in area of ​​648 Ha in planting season I and 5.416 Ha in planting season II. The results of the calculation of the wet year water balance were in total surplus, but each sub-watershed experienced a deficit in sub-watershed B in November I – December II. For this wet year, the raw water can be increased by 2,76 m3/sec for irrigation area, there is an increase of 328 Ha in planting season I and 3.862 in planting season II, ​​while in swamp irrigation area there is an increase of 648 Ha in planting season I and 5.416 Ha in planting season II.